Pengembangan Buku Elektronik Interaktif PANCAKU Berbasis Pembelajaran Penemuan untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar dalam Pendidikan Kewarganegaraan - Depi Lestari; Erik Aditya Ismaya; Yuni Ratnasari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
Pancasila and Civic Education learning in elementary schools still faces challenges in the form of low student learning outcomes due to the use of less interactive learning media and less than optimal implementation of learning models. This study aims to develop and test the effectiveness of the PANCAKU interactive e-book based on the Discovery Learning Model on the learning outcomes of fifth-grade elementary school students in Gabus Regency. This study uses the Research and Development (R&D) method based on the Borg and Gall model, which includes needs analysis, product design, development, expert validation, limited trials, revisions, and field tests. The research subjects consisted of 30 fifth-grade elementary school students. Data were collected through questionnaires, observations, and learning outcome tests in the form of pretests and posttests, and analyzed using descriptive and quantitative techniques. The results show that the PANCAKU e-book is categorized as very valid with an expert validation score of 88.6% and practical with a positive student response rate of 90.2%. The effectiveness of the media was shown by an increase in the average score of learning outcomes from 68.0 in the pretest to 82.4 in the posttest, as well as an increase in learning mastery from 35% to 87%, exceeding the minimum mastery criteria.